Effect of Mefloquine, a Gap Junction Blocker, on Circadian Period2 Gene Oscillation in the Mouse Suprachiasmatic Nucleus - Jinmi Koo; Han Kyoung Choe; Hee-Dae Kim; Sung Kook Chun; Gi Hoon Son; Kyungjin Kim (Endocrinology and Metabolism, 2015)
BackgroundIn mammals, the master circadian pacemaker is localized in an area of the ventral hypothalamus known as the suprachiasmatic nucleus (SCN). Previous studies have shown that pacemaker neurons in the SCN are highly coupled to one another, and this coupling is crucial for intrinsic self-sustainability of the SCN central clock, which is distinguished from peripheral oscillators. One plausible mechanism underlying the intercellular communication may involve direct electrical connections mediated by gap junctions.MethodsWe examined the effect of mefloquine, a neuronal gap junction blocker, on circadian Period 2 (Per2) gene oscillation in SCN slice cultures prepared from Per2::luciferase (PER2::LUC) knock-in mice using a real-time bioluminescence measurement system.ResultsAdministration of mefloquine causes instability in the pulse period and a slight reduction of amplitude in cyclic PER2::LUC expression. Blockade of gap junctions uncouples PER2::LUC-expressing cells, in terms of phase transition, which weakens synchrony among individual cellular rhythms.ConclusionThese findings suggest that neuronal gap junctions play an important role in synchronizing the central pacemaker neurons and contribute to the distinct self-sustainability of the SCN master clock.